The turn-on : how the powerful make us like them--from Washington to Wall Street to Hollywood - Goldstein, Steven (HarperBusiness, an imprint of HarperCollinsPublishers, 2019)
"What makes us love Ellen DeGeneres and hate Anne Hathaway? How do politicians move away from policy talk and connect with their voters? Activist and former producer Steven Goldstein breaks down the industry of creating likability and how public figures manufacture their image"--